NATURE AND CHARACTERISTICS OF SOIL AFFECTING THE GROWTH OF AREN PLANT (Arenga pinnata (Wurmb.) Merr) - Rosi Widarawati; Prapto Yudono; Didik Indradewa; Sri Nuryani Hidayah Utami (Agros Journal of Agriculture Science, 2017)
Aren plant (Arenga pinnata) can produce industrial raw materials. Almost all parts of palm trees can be utilized, namely young and old leaves, young endosperms, stems, stem bunches of flowers, roots, and fibers. Sugar leaves used for the roof of the house or hut. Young endosperms are used for fleas as a mixture of food or drink. Stem aren tree can be taken flour for the manufacture of palm flour. The main problem is the unclear growth of aren trees caused by soil characteristics in various places. The objectives of the study were to: 1) understanding the effect of land characteristic on the growth of aren trees; 2) look for various growth characters of aren plants at different altitudes. The study was conducted by survey and observation. Location was selected by purposive sampling, i.e. areas with altitude (<600 m ASL, 600 to 700 m ASL, and> 700 m ASL). The results showed differences results. Aren plant cultivation techniques that include the way of nursery, maintenance and post harvest management not implemented in Kulonprogo region, especially Ngargosari village, Pagerharjo, and Nglinggo. There is influence of altitude factors of place, soil type, morphology, physiology, and biochemistry to growth and aren products.